Crystallization process in thin stoichiometric GeSbTe films - Claudio, D.; Laine, B.; Licea, O.; Morales-Sanchez, E.; Prokhorov, E.; Trapaga, G. (Functional Materials, 2005)
The crystallization kinetics of Ge₁Sb₂Тe₄ and Ge₂Sb₂Тe₅ films has been analyzed using results of impedance measurements, in which Bruggerman's effective medium approximation was employed, considering that the amorphous matrix contained inclusions of two different crystalline phases. To validate the predictions from analytical model, we compared those with experimental results obtained for Ge₁Sb₂Тe₄ and Ge₂Sb₂Тe₅ films. The proposed analytical model allows us to simulate similar transformation curves as those obtained from the experiments in different materials. Кiнетику процесiв кристалiзацii у плiвках Ge₁Sb₂Тe₄ и Ge₂Sb₂Тe₅ проаналiзовано за допомогою вимiрювань iмпедансу з використанням наближення Бруггермана, яке бере до уваги наявнiсть включень двох рiзних кристалiчних фаз в аморфнiй матрицi. Прогнози аналiтичноi моделi зiставлено з експериментальними результатами для Ge₁Sb₂Тe₄ та Ge₂Sb₂Тe₅ . 3апропонована аналiтична модель дозволяє моделювати кривi фазових перетворень, аналогiчнi одержаним експериментально для рiзних матерiалiв. Кинетика процессов кристаллизации в пленках Ge₁Sb₂Тe₄ и Ge₂Sb₂Тe₅ проанализирована с помощью измерений импеданса с использованием приближения Бруггермана, учитывающего наличие включений двух различных кристаллических фаз в аморфной матрице. Предсказания аналитической модели сравнены с экспериментальными результатами для Ge₁Sb₂Тe₄ и Ge₂Sb₂Тe₅. Предложенная аналитическая модель позволяет моделировать кривые фазовых превращений, подобные полученным экспериментально для различных материалов.